Social Representations about Safety among Students and Teachers - Gilemkhanova E.N (Moscow State University of Psychology and Education, 2021)
The relevance of the study is due to the role that social ideas play in the regulation of behavior and the formation of a system of relations among subjects of the educational environment in conditions of special attention to the safety of the educational environment of the school, provoked by destructive precedents among young people (school shooting, near-football, bullying, anarchism, neo-Nazism, etc.). J. Abric's "Central system, peripheral system" concept was the theoretical framework of this study of ZhK. Aprica. The research hypothesis was based on the idea that violations of the psychological safety of the educational environment are caused by the problem of correlating nuclear and peripheral social representations about safety among different participants in educational settings. We use the prototypical analysis of P. Verges to study social representations of safety. The study sample was 137 students of the 7th grade (72 male, 65 female), 416 students of the 8th grade (201 male, 215 female), 490 students of the 9th grade (201 male, 289 female), 154 students of the 10th grade (84 male, 70 female), 117 students of the 11th grade (50 male, 67 female) and 20 teachers (1 male, 19 female). The results of the study demonstrate that 1) according to social representations about safety, students and teachers have diametrically opposed views on the role of the teacher in ensuring a safe educational environment; 2) students, who highly assess the safety of the educational environment, have active external and internal protection social representations about safety; students who rate the safety of the educational environment, have social representations in the context of passive protection; 3) the analysis of three age categories shows a tendency of the social representations about safety from the norm (students in grades 7-8) through external protection (high school students) to the internal individual resources (high school students and teachers). The new research data obtained on the peculiarities of representations about the safety of students and teachers can become the basis for understanding the growing tension in the field of the safety of the educational environment and the frequent incidents of its violation.